The Epstein-Barr Virus Immediate-Early Gene Product, BRLF1, Interacts with the Retinoblastoma Protein during the Viral Lytic Cycle - Zacny, Valerie L. (American Society for Microbiology, 1998)
Retinoblastoma protein (Rb) is a key regulator of cellular proliferation, controlling entry into G(1)/S in the cell cycle, largely through its action in binding the cellular transcription factor E2F, which activates genes important in DNA synthesis. Small DNA tumor viruses encode gene products which can functionally inactivate Rb, promoting cellular proliferation and viral DNA synthesis. In this study, the Epstein-Barr virus (EBV) immediate-early lytic gene product, BRLF1 (R), is shown to bind Rb in vivo, shortly after induction of the viral lytic cycle in EBV-infected Akata cells. Furthermore, the temporal kinetics of R-Rb interaction correlate with displacement of E2F1 from Rb. Mapping of the domains required for the interaction of R and Rb proteins reveals that R binds specifically to the N terminus of Rb, outside the Rb pocket, and that the first 200 amino acids of R are required for this interaction. The interaction of R and Rb may initiate cell cycle progression and facilitate viral DNA synthesis during lytic replication.